2000
DOI: 10.4049/jimmunol.164.11.5905
|View full text |Cite
|
Sign up to set email alerts
|

Improving Protective Immunity Induced by DNA-Based Immunization: Priming with Antigen and GM-CSF-Encoding Plasmid DNA and Boosting with Antigen-Expressing Recombinant Poxvirus

Abstract: Intramuscular immunization with a naked DNA plasmid expressing the Plasmodium yoelii circumsporozoite protein (pPyCSP) protects mice against challenge with P. yoelii sporozoites. This protection can be improved either by coadministration of a plasmid expressing murine GM-CSF (pGMCSF) or by boosting with recombinant poxvirus expressing the PyCSP. We now report that combining these two strategies, by first mixing the priming dose of pPyCSP with pGMCSF and then boosting with recombinant virus, can substantially i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 27 publications
5
74
0
2
Order By: Relevance
“…Second, recent experiments have shown marked improvements in immunogenicity and efficacy when DNA vaccines are used as part of a heterologous prime-boost vaccination strategy. 19,20,15 It was possible that boosting with recombinant virus would overcome whatever suppressive effect of mixing was observed with DNA vaccines alone. However, in the current experiments, boosting with either of two recombinant vaccinia expressing PfCSP only partially overcame the suppressive effect of mixing on antibody responses to PfCSP (Figure 4a), and had no effect on the suppression of PfCSP-specific IFN-g responses in M9 (Figure 4b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, recent experiments have shown marked improvements in immunogenicity and efficacy when DNA vaccines are used as part of a heterologous prime-boost vaccination strategy. 19,20,15 It was possible that boosting with recombinant virus would overcome whatever suppressive effect of mixing was observed with DNA vaccines alone. However, in the current experiments, boosting with either of two recombinant vaccinia expressing PfCSP only partially overcame the suppressive effect of mixing on antibody responses to PfCSP (Figure 4a), and had no effect on the suppression of PfCSP-specific IFN-g responses in M9 (Figure 4b).…”
Section: Discussionmentioning
confidence: 99%
“…Detection of antigen-specific IFN-g-producing cells was performed as previously described, 15 with minor modifications. Spleen cells from immunized mice were incubated with previously identified H-2 d restricted Tcell epitopes from antigens of interest, PfCSP(7G8) 39-47 NYDNAGTNL, PfEXP1(3D7) 66-80 EVNKRKSKYK-LATSV, and PfLSA1(3D7) 1671-1679 YYIPHQSSL.…”
Section: Ifn-g Elispotmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous murine studies showed that coadministration of murine GM-CSF with P. yoelii CSP plasmid enhanced antibody responses and protective immunity in BALB/c mice. 13,14 Since no antibodies were produced in the first single-gene human trials with PfCSP DNA vaccine, 10,11 human GM-CSF was coadministered with the five-gene mixture vaccine in some of the groups in Preclinical studies with a multigene-malaria DNA vaccine M Sedegah et al the MuSTDO 5 human trial; the analysis of this study is in preparation (TL Richie, unpublished). However, our results here demonstrated that the effects of coadministration of a plasmid expressing mGM-CSF with Pf plasmids are not consistent.…”
Section: Discussionmentioning
confidence: 99%
“…One of the best methods to enhance the immunogenicity of DNA vaccines, particularly antibody response in mice, has been co-immunization with a plasmid expressing granulocyte-macrophage colony-stimulating factor (GM-CSF). 13,14 Based upon the results of these previous studies, the decision was made to produce under good manufacturing practice (GMP) conditions five plasmids (four already studied), each of which expressed a different Plasmodium falciparum protein, PfCSP, PfSSP2, PfExp1, PfLSA1, and PfLSA3. The rationale for the choice of the five proteins has been described.…”
Section: Introductionmentioning
confidence: 99%